2019
DOI: 10.1002/cncr.32165
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, visceral adiposity, and prostate cancer: What is the role of lifestyle interventions?

Abstract: The findings from Dickerman et al's research highlight the need to consider and implement lifestyle interventions to target weight loss and the risk of prostate cancer. Interventions that combine 2 lifestyle behaviors, diet and exercise, may be most impactful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Prostate cancer represents the second cause of cancer-related death in men in the US and the third in Europe ( 10, 11 ). Although AR signaling is the major driver of the disease, evidence is accumulating that obesity and high consumption of saturated FAs contribute to the development of more advanced and lethal prostate cancer ( 12, 13, 42, 58 ). This is particularly worrisome in Western countries where prostate cancer incidence is rising and both obesity and consumption of unhealthy diets are increasing at alarming rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate cancer represents the second cause of cancer-related death in men in the US and the third in Europe ( 10, 11 ). Although AR signaling is the major driver of the disease, evidence is accumulating that obesity and high consumption of saturated FAs contribute to the development of more advanced and lethal prostate cancer ( 12, 13, 42, 58 ). This is particularly worrisome in Western countries where prostate cancer incidence is rising and both obesity and consumption of unhealthy diets are increasing at alarming rates.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is the second cause of cancer-related death in men in the United States, and the third in Europe ( 10, 11 ). Obesity status, lifestyle, and environmental factors, including diet, profoundly affect the course of the disease ( 12 ). Although the association between obesity and worse prostate cancer progression/lethality is well established ( 13 ), the link between increased consumption of saturated fatty acids (FA) and fatal prostate cancer is still the object of debate ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“… 28 Number of recent studies reported that VO is more reliable clinical marker for predicting outcome than traditional view on obesity defined by BMI. 29 , 30 , 31 , 32 , 33 The useful predictor of VO is visceral-to-subcutaneous adipose tissue area ratio (VSR), and high VSR is associated with poor oncologic outcome. 34 , 35 , 36 , 37 Also, another body composition abnormality, the new concept of sarcopenic obesity (SO), a combination of excess adiposity and sarcopenia, seems to have powerful negative prognostic impact in oncology treatment and is gaining increased attention in cancer research.…”
Section: Introductionmentioning
confidence: 99%